1997
DOI: 10.3136/fsti9596t9798.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tea Extracts and Phenolic Components on Immunoglobulin Production by Mesenteric Lymph Node Lymphocytes of Sprague-Dawley Rats.

Abstract: We examined the effect of tea extracts on immunoglobulin (Ig) production of mesenteric lymph node lymphocytes of Sprague-Dawley rats and found that various extracts suppressed the production of lgA, IgG, and lgM. In addition, the original extracts of green and black teas strongly enhanced lgE production, and their 10' or 103 times diluted samples exerted an inhibitory effect. Similarly, tea polyphenols having a triphenol group enhanced lgE production at I mM and inhibited it at concentrations below 100 pM. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…These results suggest that the pyrogallol-type structure, such as the pyrogalloltype B-ring or galloyl group, is an important factor in the phagocytic activity of VD3-differentiated HL60 cells. This is similar to the results of Yamada et al (1997), who showed that pyrogallol-type polyphenols, such as EGCG, gallic acid and pyrogallol, enhanced Polyphenols with a pyrogallol-type structure induce the apoptosis of malignant cells through a caspase signaling pathway (Saeki et al 2000;Hayakawa et al 2001;Vergote et al 2002); however, caspase is a protease playing an important role not only in apoptosis but also in innate immunity (Martinon and Tschopp 2004;Winoto 2004), and regulates phagocytic activity in macrophages, such as dendritic cells (Ho et al 2009); therefore, we investigated the involvement of the caspase pathway in phagocytic activity. As shown in Fig.…”
Section: Resultssupporting
confidence: 94%
“…These results suggest that the pyrogallol-type structure, such as the pyrogalloltype B-ring or galloyl group, is an important factor in the phagocytic activity of VD3-differentiated HL60 cells. This is similar to the results of Yamada et al (1997), who showed that pyrogallol-type polyphenols, such as EGCG, gallic acid and pyrogallol, enhanced Polyphenols with a pyrogallol-type structure induce the apoptosis of malignant cells through a caspase signaling pathway (Saeki et al 2000;Hayakawa et al 2001;Vergote et al 2002); however, caspase is a protease playing an important role not only in apoptosis but also in innate immunity (Martinon and Tschopp 2004;Winoto 2004), and regulates phagocytic activity in macrophages, such as dendritic cells (Ho et al 2009); therefore, we investigated the involvement of the caspase pathway in phagocytic activity. As shown in Fig.…”
Section: Resultssupporting
confidence: 94%
“…In this study, epigallocatechin gallate (EGCG; Sigma-Aldrich Co., St. Louis MO, USA), a tea catechin, was used as a typical natural inhibitor, since EGCG is well known to possess anti-allergic effect via various inhibition mechanisms (Tachibana, 2011;Yamada, Watanabe, Kaku, Hassan, & Sugano, 1997;Yoshino, Kawaguchi, Yamazaki, & Sano, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Though EC and ECg have diphenolic B ring and EGC and EGCg have triphenolic B ring, it has been reported that triphenolic compounds enhance IgA production of rat lymphocytes, but diphenolic compounds does not [4]. These compounds have been reported to exert diverse biological effects, such as anti-viral, anti-mutagenic, anti-cancer, and anti-allergic activities.…”
Section: Regulation Of Immunoglobulin Production By Anti-oxidative Comentioning
confidence: 99%